Accuracy of elastic fusion biopsy in daily practice: Results of a multicenter study of 2115 patients. (5th September 2018) - Oderda, Marco; Marra, Giancarlo; Albisinni, Simone; Altobelli, Emanuela; Baco, Eduard; Beatrici, Valerio; Cantiani, Andrea; Carbone, Antonio; Ciccariello, Mauro; Descotes, Jean‐Luc; Dubreuil‐Chambardel, Marine; Eldred‐Evans, David; et al.
Abstract : Objectives: To assess the accuracy of Koelis fusion biopsy for the detection of prostate cancer and clinically significant prostate cancer in the everyday practice. Methods: We retrospectively enrolled 2115 patients from 15 institutions in four European countries undergoing transrectal Koelis fusion biopsy from 2010 to 2017. A variable number of target (usually 2–4) and random cores (usually 10–14) were carried out, depending on the clinical case and institution habits. The overall and clinically significant prostate cancer detection rates were assessed, evaluating the diagnostic role of additional random biopsies. The cancer detection rate was correlated to multiparametric magnetic resonance imaging features and clinical variables. Results: The mean number of targeted and random cores taken were 3.9 (standard deviation 2.1) and 10.5 (standard deviation 5.0), respectively. The cancer detection rate of Koelis biopsies was 58% for all cancers and 43% for clinically significant prostate cancer. The performance of additional, random cores improved the cancer detection rate of 13% for all cancers ( P < 0.001) and 9% for clinically significant prostate cancer ( P < 0.001). Prostate cancer was detected in 31%, 66% and 89% of patients with lesions scored as Prostate Imaging Reporting and Data System 3, 4 and 5, respectively. Clinical stage and Prostate Imaging Reporting and Data System score were predictors of prostate cancer detection in multivariate analyses. Prostate‐specific antigen was associated with prostate cancer detection only for clinically significant prostate cancer. Conclusions: Koelis fusion biopsy offers a good cancer detection rate, which is increased in patients with a high Prostate Imaging Reporting and Data System score and clinical stage. The performance of additional, random cores seems unavoidable for correct sampling. In our experience, the Prostate Imaging Reporting and Data System score and clinical stage are predictors of prostate cancer and clinically significant prostate cancer detection; prostate‐specific antigen is associated only with clinically significant prostate cancer detection, and a higher number of biopsy cores are not associated with a higher cancer detection rate.